A SOCIOLINGUISTIC STUDY ON REGISTERS USED IN STREETBALL GAME(A CASE STUDY OF REGISTER IN SOLO STREETBALL) - Susilo, Agus (2010)
The research is about describing the registers used in streetball games. The aims of the study are to identify the forms of registers used in streetball games, to describe the meaning and the function of registers used in streetball games. In this research, the writer uses a descriptive qualitative method. The data are the vocabularies as registers used in streetball games in the form of words and compound word. The writer applies observation and documentation method to collect the data. The data are analyzed based on their linguistics forms, their meaning and their function. In identifying the form, the writer uses syntactical analysis. In analyzing the meaning of the register, the writer employs the theory proposed by Halliday. The results of the research show that; 1) the linguistic forms of the register are divided into two, they are: words and compound words. The word consists of two categories; noun, and verb. The compound word consists of two categories; noun, and adjective. 2) the meaning of sports registers used in streetball games are divided into three categories, they are; a) based on the fields: when the player feels happy, when a player is disappointed, when the player is angry, when the MC gives information. b) based on the mode the register is used in oral language. c) based on the tenor, the register is used among the player, and the MC of the game.